2015
DOI: 10.1371/journal.pone.0126645
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically Distant Viruses Use the Same BH3-Only Protein Puma to Trigger Bax/Bak-Dependent Apoptosis of Infected Mouse and Human Cells

Abstract: Viruses can trigger apoptosis of infected host cells if not counteracted by cellular or viral anti-apoptotic proteins. These protective proteins either inhibit the activation of caspases or they act as Bcl-2 homologs to prevent Bax/Bak-mediated outer mitochondrial membrane permeabilization (MOMP). The exact mechanism by which viruses trigger MOMP has however remained enigmatic. Here we use two distinct types of viruses, a double stranded DNA virus, herpes simplex virus-1 (HSV-1) and a positive sense, single st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“… 5 , 37 Furthermore, we recently reported that cells that expressed a dominant negative (DN) form of I κ Bα displayed high levels of apoptosis when infected with wild type HSV-1. 31 These results support a role for NF- κ B activation in preventing apoptosis during HSV infection that can vary with respect to the context and the ability of the cells to sustain virus replication. Thus, resolving the intricate interplay between NF- κ B signalling, apoptosis and HSV-1 replication remains an intriguing issue to better understand the complex processes controlling HSV infectious cycle and the restriction of infection in some cell types.…”
supporting
confidence: 62%
See 2 more Smart Citations
“… 5 , 37 Furthermore, we recently reported that cells that expressed a dominant negative (DN) form of I κ Bα displayed high levels of apoptosis when infected with wild type HSV-1. 31 These results support a role for NF- κ B activation in preventing apoptosis during HSV infection that can vary with respect to the context and the ability of the cells to sustain virus replication. Thus, resolving the intricate interplay between NF- κ B signalling, apoptosis and HSV-1 replication remains an intriguing issue to better understand the complex processes controlling HSV infectious cycle and the restriction of infection in some cell types.…”
supporting
confidence: 62%
“…Interestingly, we have recently demonstrated that apoptosis by HSV-1 in monocytic cells depends on Bax/Bak and the BH3-only Puma protein. 31 In addition, Bcl-2 overexpression in U937 monocytic cells infected with HSV-1 31 or HSV-2 32 leads to an increase of virus yield, further supporting the notion that virus replication in this cell type can be strongly affected by modulating the apoptotic pathway.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…A possible cause of HSV-1-mediated neural dysfunction is the activation of apoptotic pathways and intra-axonal degradation, which are driven by the axon's local indirect and direct responses to the viruses themselves in susceptible phenotypes. Studies have suggested that viruses use abnormal expressions of p53 upregulated modulator of apoptosis (PUMA) [30] and/or innate immunity signaling molecule (SARM1) [31,32] to trigger axon degeneration. This implies that PUMA and/or SARM may play an important role in HSV-1-mediated neural dysfunction.…”
Section: Viral Infectionmentioning
confidence: 99%
“…The activation of PUMA by nongenotoxic stimuli is p53‐independent and mediated by different transcription factors, including p53 homologue p73, forkhead box O3a (FoxO3a), and nuclear factor‐kappa B (NF‐κB) . Upon induction, PUMA facilitates mitochondrial outer membrane permeabilization and caspase activation cascade to regulate Bcl‐2‐associated X protein (Bax) activity . PUMA‐deficient colorectal cancer cells eliminate mitochondrial apoptosis caused by various stimuli .…”
Section: Introductionmentioning
confidence: 99%